COMMUNITY-BASED WATER RESOUCE MANAGEMENT IN MALADUK VILLAGE KLAMONO AND KLASAFET DISTRICTS, SORONG WEST PAPUA INDONESIA - Nonon Saribanon; Hariyanto; Panji B Surata Azis (Journal of Social Political Sciences, 2022)
Citizens of Maladuk village only use the water from the Klasafet’s river for their daily needs. However, the river is not suitable for hygiene and health standards. As a solution and corresponding with corporate social responsibility, the CSR program from PT Pertamina EP Papua Field in collaboration with the Ministry of PUPR succeeded in improving the water quality of the Klasafet’s river through the Communal Biosand Water Filter innovation. This tool helps the Maladuk community obtain water that can be used for bathing, washing, latrines, and industrial needs. With the filtering method, raw water from the river can be processed up to 59,000 liters/day to be clearer. Up to now, the beneficiaries of clean water from the Klasafe’s river have reached 1,808 families or around 6,000, people.